The Effect of Massage Stimulation on Anthropometric Measures of Preschool Aged Children at Integrated PAUD Merpati Anggrek Surabaya - Setiawandari, Setiawandari (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Massage stimulation is a traditional therapy of the Indonesian, which combines auditory, visual and tactile kinesthetic stimuli, which can be given from early to unlimited age. Massage stimulation for preschoolers in addition to relaxing the child is also reducing stress, increasing immunity, stimulating the vagus nerve, also increasing growth by stimulating cell growth. This research aims to determine the effect of massage stimulation on the anthropometric size of preschoolers. This research method uses Randomized Controlled Trial. The results obtained a significant value of p = 0,000 or p <0.05 in the treatment group, but in the two control groups there was no difference in anthropometric measurements of height and head circumference p> 0.05. In conclusion, there was the effect of massage stimulation on body weight, height, upper arm circumference and head circumference. But the height and head circumference were not found differences in the two groups.